The Effect of Interpersonal Justice In Family And Decision Making for Healthy Life On Students’ Health Behavior - Guspri Devi Artanti (Universitas Negeri Jakarta, 2017)
The research is about studying the effect of interpersonal justice in the family and decision making to healthy life on students’ health behavior. There are around 5 research problems have been solved, including interaction effect of both interpersonal justice in the family and decision-making to healthy life on students’ health behavior. Therefore, an ex-post facto with 2 x 2 factorial design had been applied. Each cell consisted of 21 students’ from Senior High School in East Jakarta which selected randomly. On this study, there were three instruments have been developed, Health Behavior (HB), Interpersonal Justice in the family (IJ), and Decision Making for healthy life (DM) which measured in scaling form. Its reliability respectively was .94 (HB), .93 (IJ), and .89 (DM). Data have been analyzed by applying two-way ANOVA. Research results show that there is highly significant difference of students’ health behavior between strong and weak interpersonal justice in family. Highly significant difference of students’ health behavior also found between those students’ who is high and low decision making for healthy life. Finally, there is no significant interaction effect found between interpersonal justice in family and decision making for healthy life on students’ health behavior. Based on those findings, it could be that students’ health behavior might have been affectied by interpersonal justice independently without considering students’ decision making for healthy life. If students’ health behavior would be improved, interpersonal justice in family and decision making could be taken in to consideration separately.